Menstrual Abnormalities and Associated Hormone Profile In Chronic Kidney Disease Stage 5 Patients - Jabin, Masrura; Chowdhury, Md Nizamuddin; Islam, Md Nazrul; Uddin Khan, Mohammad Ehasun (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Although menstrual abnormalities and associated hormonal dysregulations are very common in the reproductive age group of Chronic Kidney Disease (CKD) patients, this remains a neglected area. This field had been poorly explored in last ten years worldwide and a few research regarding this area in Bangladesh as well. Aim: To evaluate menstrual abnormalities occurring in CKD stage 5 (CKD5)patients undergoing twice-weekly and thriceweekly maintenance hemodialysis (HD) also in non-dialytic CKD5 patients and to provide more detail information on hormone profile (FSH, LH, Prolactin, Estradiol) of these patients. Materials and method: This obsevational study was conducted in the Department of Nephrology, DMCH, the sample population was also collected from BSMMU and NIKDU from April 2017 to March 2018. A total of 51 CKD stage 5 patients were enrolled in this study. Among them, 34 patients were dialytic (17 of them were taking twice weekly HD and 17 of them were taking thrice weekly HD) and 17 non-dialytic patients at reproductive age were evaluated. Detailed menstrual histories, thorough clinical examinations as well as investigations were done in all the patients. Serum FSH, LH, Estradiol, and Prolactin were evaluated using chemiluminescence immunoassay in the Department of Microbiology of BSMMU. Statistical analysis of the study was done by SPSS-24. The confidence interval was considered at 95% level. P-value <0.05 was considered statistically significant. Results: 100% of non-dialytic CKD5 women had menstrual disorders (72% of patients had secondary amenorrhea, 18% had oligomenorrhoea and 10% had menometrorrhagia). And 73.52% of patients in the HD group had menstrual disorders (29% patients had regular menstruation, 28.5% had secondary amenorrhea, 23.5% had oligomenorrhoea and 19% had menometrorrhagia). With continuation of HD amenorrhea disappeared in 43% of patients in the thrice-weekly HD group, also 22.22% patients in the twice-weekly HD group regained menstruation. Serum LH and prolactin levels were significantly higher in the non-HD group compared to the HD group (p<0.05). Estradiol levels were also higher in HD patients than the non-HD patients. LH and Prolactin levels were also higher in the twice-weekly HD group compared to the thrice-weekly HD group. In the secondary amenorrheic group, serum FSH, LH, Prolactin levels were significantly higher than the other groups having menstrual disorder (p<0.05). Conclusion: Menstrual abnormalities and associated hormonal dysregulations were significantly lower in thriceweekly HD patients compared to the twice-weekly HD patients and significantly lower in twice-weekly HD patients compared to the non-dialytic CKD5 patients. Besides, it is suggested that long-duration dialysis might improve menstrual disorders in such patients as prolactin, LH levels gradually decreased with longer duration of dialysis. J Bangladesh Coll Phys Surg 2022; 40: 45-51